Family Business Succession Planning, Entrepreneurial Orientation and Firm Performance Among Small and Medium Enterprises - Nyalita, Angela M. (Machakos University, 2018)
Family-owned businesses continue to form the backbone of most of the national economies. However, because of the tenuous nature of the ownership structure of most family businesses only one in three family businesses succeeds in making it to the second generation. These smaller businesses are particularly vulnerable to the impact of unexpected, life-altering events that affect the business owner and often the business itself, therefore need to consider proper succession of the businesses. The paper therefore seeks to review literature on the relationship between planning, family business succession entrepreneurial orientation and firm performance of small and medium enterprises. The review also gives the back ground of the study on family business and their role in economic development ,having successful succession planning in mind. The aim is to shed some light on what other scholars have written about the role of family business succession planning and entrepreneurial orientation on firm performance. The paper also looks at the theoretical foundation of entrepreneurship that gives a firm foundation of study. Keywords: Family business Succession planning, Entrepreneurial Orientation and firm performance.
Keywords: Family business